2014
DOI: 10.1371/journal.pone.0109500
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Cycling of Lake Kivu (East Africa): Net Autotrophy in the Epilimnion and Emission of CO2 to the Atmosphere Sustained by Geogenic Inputs

Abstract: We report organic and inorganic carbon distributions and fluxes in a large (>2000 km2) oligotrophic, tropical lake (Lake Kivu, East Africa), acquired during four field surveys, that captured the seasonal variations (March 2007–mid rainy season, September 2007–late dry season, June 2008–early dry season, and April 2009–late rainy season). The partial pressure of CO2 (pCO2) in surface waters of the main basin of Lake Kivu showed modest spatial (coefficient of variation between 3% and 6%), and seasonal variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 93 publications
(153 reference statements)
3
30
1
Order By: Relevance
“…As the depth profile of δ 13 C-DIC revealed that the DIC pool was isotopically lighter in the bottom of the mixolimnion, Overall, the data suggest that the input of DIC originating from the monimolimnion during the dry season had a strong influence on δ 13 C-DIC in the mixolimnion, but the seasonal variability of δ 13 C-DIC observed in the mixed layer holds information on biological processes. The gradual increase with time of the δ 13 C-DIC in the mixed layer supports the conclusions of other studies carried out in Lake Kivu Borges et al, 2014) which showed, based on a detailed DIC and DI 13 C mass balance approach and several microbial processes measurements, that photosynthetic CO 2 fixation should exceed the respiration of OM. Indeed, in Lake Kivu, riverine inputs of allochthonous OM from the catchment (0.7-3. the Ruzizi River is also relatively low and was computed to be 0.6 mmol m −2 d −1 (this study) based on the long-term discharge average of Ruzizi (83.2 m 3 s −1 , Borges et al, 2014), the average POC and DOC in surface waters (0.052 and 0.142 mmol L −1 , this study).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…As the depth profile of δ 13 C-DIC revealed that the DIC pool was isotopically lighter in the bottom of the mixolimnion, Overall, the data suggest that the input of DIC originating from the monimolimnion during the dry season had a strong influence on δ 13 C-DIC in the mixolimnion, but the seasonal variability of δ 13 C-DIC observed in the mixed layer holds information on biological processes. The gradual increase with time of the δ 13 C-DIC in the mixed layer supports the conclusions of other studies carried out in Lake Kivu Borges et al, 2014) which showed, based on a detailed DIC and DI 13 C mass balance approach and several microbial processes measurements, that photosynthetic CO 2 fixation should exceed the respiration of OM. Indeed, in Lake Kivu, riverine inputs of allochthonous OM from the catchment (0.7-3. the Ruzizi River is also relatively low and was computed to be 0.6 mmol m −2 d −1 (this study) based on the long-term discharge average of Ruzizi (83.2 m 3 s −1 , Borges et al, 2014), the average POC and DOC in surface waters (0.052 and 0.142 mmol L −1 , this study).…”
Section: Discussionsupporting
confidence: 89%
“…The gradual increase with time of the δ 13 C-DIC in the mixed layer supports the conclusions of other studies carried out in Lake Kivu Borges et al, 2014) which showed, based on a detailed DIC and DI 13 C mass balance approach and several microbial processes measurements, that photosynthetic CO 2 fixation should exceed the respiration of OM. Indeed, in Lake Kivu, riverine inputs of allochthonous OM from the catchment (0.7-3. the Ruzizi River is also relatively low and was computed to be 0.6 mmol m −2 d −1 (this study) based on the long-term discharge average of Ruzizi (83.2 m 3 s −1 , Borges et al, 2014), the average POC and DOC in surface waters (0.052 and 0.142 mmol L −1 , this study). It implies that the outputs of OM (9.4 + 0.7 = 10.1 mmol m −2 d −1 ) are higher than the inputs of OM from the catchment (0.7-3.3 mmol m −2 d −1 ) suggesting a net autotrophic status of Lake Kivu.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations